Impact Of COVID-19 On The Entrepreneurs In The Tourism Sector In Batticaloa District, Sri Lanka - Navirathan, V.; Vijayakumar, S.; Jeyarajah, S. (Faculty of Commerce and Management, Eastern University, Sri Lanka, 2023)
Tourism is one of the fastest growing sectors in Asia and is the third largest foreign exchange earner in Sri Lanka. When the COVID- 19 pandemic surfaced in 2020, tourism was one to face the immediate impact and one of the industries to be strained the most. The effects of COVID-19 on tourism entrepreneurs in Sri Lanka's Batticaloa district are the focus of this article. This study set out to figure out how COVID-19 would affect entrepreneurs in the tourism industry economically and through investment. This research took quantitative and qualitative approaches. The questionnaires and in-person interviews were used to collect the data. Fifty tourism entrepreneurs were interviewed randomly from the Kalkudah Division, the most well-known tourist destination in the Batticaloa district. The research findings indicate that negative relationship between the COVID-19 and entrepreneurs' income and investment. Therefore, the present study recommends that convalescing measures to be implemented during disasters in the tourism sector in Sri Lanka.
Keywords: Impact of COVID-19; Tourism Sector; Economic Impacts; Investment Impact